KONSTRUKSI KREATIF PEMEROLEHAN KOMPETENSI PRAGMATIK ANAK USIA PRASEKOLAH - Werdiningsih, Dyah (Diksi, 2008)
This article is about a research conducted with the objective of studyingthe process of creative construction, which consists of a process of hypothesisformulation and that of hypothesis testing, in Javanese-Indonesian bilingualpreschool children's acquisition of pragmatic competence in using Indonesian.Employing a longitudinal research design, the research used subjects of differentages: preschool children 2, 3, 4, and 5 years of age. The data were compiled bymeans of observations together with data recording by using electronic recordingequipment and field-note data cards. The data were analyzed by using a techniqueof performance analysis. On the basis of the data analysis, it has been found that thecreative construction in the acquisition of pragmatic competence has been seen inpreschool-age children's use of learning strategies, which consist of two types:cognitive and social strategies.Keywords: creative construction, pragmatic competence, child learners